Cementoblastoma presenting as swelling on the left maxilla : a case report - Ghazali, Ahmad Badruddin (2021)
Introduction: Cementoblastoma is usually diagnosed in the second decade of life, most commonly affecting the first permanent mandibular molar tooth. It is usually diagnosed from the radiographic examination and confirmed by the histopathology examination. Objective: To report a case of cementoblastoma affecting a teenage girl and presented as swelling on the left side of the maxilla. Case: A patient complained of a painless, slow-growing mass on her left maxilla for six months. Plain radiographs showed a well-defined radiopaque lesion surrounded by radiolucent rim associated with tooth 26 with homogenous radiopaque internal structure and causing displacement of neighbouring tooth 25. Further radiographic examination with cone-beam computed tomography (CBCT) revealed greater detail of the lesion. Surgical treatment was done, and histopathology examination confirmed the diagnosis of cementoblastoma. Conclusion: Careful radiographic interpretation is essential for diagnosing cementoblastoma, which all clinicians should always be aware.